Pengaruh Perencanaan Pajak, Kesulitan Keuangan dan Strategi Bisnis Perusahaan terhadap Manajemen Laba - Rara Ayu, Melliana; Ajimat, Ajimat (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study aims to analyze the effect of tax planning, financial distress, and corporate business strategy on earnings management in property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The sample used in this study was 8 property and real estate companies listed on the Indonesia Stock Exchange during the period 2019 to 2023 using a purposive sampling technique. The data used in this study are secondary data in the form of financial reports from each company that has been used as a research sample. The variables used in this study are Tax Planning (X1) as the first independent variable, Financial distress (X2) as the second independent variable, and company business strategy (X3) as the third independent variable and Earning Management (Y) as the dependent variable. The panel data regression method is used as the research methodology in this study. Analysis of the research results using the help of EViews 12 Student Version Lite software. The results showed that the bsunhaest model was the Random Effect Model (REM). The results of this study indicate that tax planning partially has no effect and is not significant on earnings management, financial difficulties partially have no effect and are not significant on earnings management, the company's business strategy partially has an effect and is significant on earnings management, and simultaneously tax planning, financial difficulties, and the company's business strategy have no effect and are not significant on earnings management.